2021
DOI: 10.1007/s43032-021-00528-z
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cell Therapy and Other Novel Treatment Approaches for Premature Ovarian Insufficiency

Abstract: Premature ovarian insufficiency (POI) is a condition characterized by amenorrhea, hypergonadotropic hypogonadism, estrogen deficiency, and reduced follicle counts leading to infertility under the age of 40. POI occurs in approximately 1-3% of women in the general population. Evaluation is warranted when the diagnosis of POI is made to rule out underlying etiologies, which could be multifactorial. This review serves to cover the novel treatment approaches reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 65 publications
0
13
0
3
Order By: Relevance
“…But long-term HRT also has certain risks, such as the occurrence of endometrial cancer and breast cancer [1]. Mesenchymal stem cell transplantation is considered to be a very promising treatment strategy for reversing the negative effects of POI [3] . One of the key events that contribute to ovarian aging includes follicular atresia as it is associated with the pyroptosis and necrosis of granulosa cells and thecal cells in aging ovaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But long-term HRT also has certain risks, such as the occurrence of endometrial cancer and breast cancer [1]. Mesenchymal stem cell transplantation is considered to be a very promising treatment strategy for reversing the negative effects of POI [3] . One of the key events that contribute to ovarian aging includes follicular atresia as it is associated with the pyroptosis and necrosis of granulosa cells and thecal cells in aging ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…Hormone replacement therapy, as a rst-line clinical treatment, can reduce the symptoms caused by estrogen de ciency, but there is still no method for restoring follicular development in failed ovaries [2] . In recent years, many studies have suggested that transplantation of stem cells may be able to restore ovarian function [3] . When mesenchymal stem cells (MSCs) were used to treat POI, there was a decrease in apoptosis of ovarian granulosa cells (GCs), recovery of ovarian function, and increased levels of sex hormones [4][5][6][7] ; however, the underlying mechanism remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying the developmental progression of human primordial follicles is unclear. However, the initial recruitment has been linked to protein kinase B (Akt) and mammalian target of rapamycin (mTOR) signaling pathways [ 6 , 22 ].…”
Section: Premature Ovarian Insufficiency (Poi)mentioning
confidence: 99%
“…For example, Yan et al transplanted MSCs to 61 patients with POF and found that the number of follicles in each developmental stage, including antral follicles, dominant follicles and mature follicles, increased significantly ( Yan et al, 2020 ). Other researchers have found that autologous MSC transplantation can trigger menstruation to resume, relieve menopausal symptoms, improve ovarian function and help patients become pregnant ( Bukovsky and Caudle, 2012 ; Igboeli et al, 2020 ; Mashayekhi et al, 2021 ; Ulin et al, 2021 ). Ling et al treated POF mice with MSCs and found that MSC transplantation could significantly restore their hormone secretion ability, improve follicular growth and GC survival, and recover the ovarian function that was destroyed by chemotherapy used to create the POF mice ( Ling et al, 2019 ).…”
Section: Mscs and Fertility Protectionmentioning
confidence: 99%